The self-reported stress and stressors in tram and long-haul truck drivers. (July 2022) - Onninen, Jussi; Pylkkönen, Mia; Hakola, Tarja; Puttonen, Sampsa; Virkkala, Jussi; Tolvanen, Asko; Sallinen, Mikael
Abstract: Work stress may compromise professional drivers' health and driving capacity. Differences between driver groups in terms of on-duty stress are understudied. Therefore, we examined self-reported stress (Stockholm University Stress Scale) of shift-working tram and long-haul truck drivers (n = 75) across 2–3 weeks. Furthermore, stressors were self-reported retrospectively and categorised as related to the job, driving conditions, personal, or other causes. Stress levels were generally low, but moderate to high stress (≥6) was more frequently reported among the tram drivers. Stressors related to the job (54%) and driving conditions (19% of all shifts) were frequently reported among the tram and truck drivers, respectively. Moderate to high stress was associated with categorised stressors related to the job and other causes among the tram drivers, and all categorised stressors among the truck drivers. Altogether, self-reported stress and stressors differ by driver group, but the role of shift type is less significant. Highlights: On-duty subjective stress is mostly low in tram and long-haul truck drivers. Occasional high levels of stress are not uncommon in either driver group. Tram drivers commonly report job-related stressors, e.g., tight schedules. Both tram and truck drivers attribute on-duty stress to driving conditions. Levels of stress or stressors are not dependent on the type of work shift.